Niagara Falls - Simons, Lisa M. B., 1969- (Natural wonders of the world (Focus Readers (Firm)), 2018)
Highlights the history of Niagara Falls from their geological formation to the plant and animal life found there. Examines the threats facing the falls, and what can be done to protect them. Includes text-related questions, a glossary, resources for further information, and color photographs.